Temporal Dynamics of Phlebotomine Sand Flies Population in Response to Ambient Temperature Variation, Bam, Kerman Province of Iran - Mansour Halimi; Zahra Zarei Cheghabaleki; Mohammad Jafari Modrek; Mahdi Delavari (Ubiquity Press, 2017)
Background Variations in climate condition may have changed the dynamic of zoonotic cutaneous leishmaniasis (ZCL) and its agents such as sand flies and reservoir in the Bam Kerman the dry region of Iran. Objectives In this study we intend to examine the seasonal and interannual dynamics of the phlebotomine mosquito as a function of ambient temperature in Bam, Kerman one of the main leshmaniasis prevalence area in Iran. Methods The MODIS land surface temperature product (LST; MODIS/Terra LST/E Monthly L3 Global 0.05Deg CMG [MOD11C3]) and land-based climatic data were used as explanatory variables. Monthly caught mosquitoes in Bam, Kerman, were used as a dependent variable. The temporal associations were first investigated by inspection of scatterplots and single-variable regression analysis. A multivariate linear regression model was developed to reveal the association between ambient temperature and the monthly mosquito abundance at a 95% confidence level (P < 0.05). Findings The findings indicated that the monthly variation of 0-10 cm of soil depth temperature is the main driver of phlebotomine mosquito temporal dynamics. The developed multivariate model also indicated that the ambient temperature variation was responsible for >0.80 of temporal dynamics of phlebotomine mosquitos in Bam.